University students’ intention to use visual learning for hospitality education in Malaysia - Nor Izzati Liyana Muhd Yasin; Nik Nor Huda Hafiza Nik Sim; Chia Choy Cheng Crystalbel; Ummi Syazana Japeri (2021)
This study focuses on university students’ intention to use visual learning for hospitality education in Malaysia. The study examines the relationships between perceived usefulness, perceived ease of use, perceived enjoyment and the use of visual learning among university students. A quantitative research is used to accomplish this study, and responses from 100 respondents are collected. Reliability test, descriptive analysis and inferential analysis were used to answer the research objectives. The results showed that all independent variables, perceived usefulness, perceived ease of use and perceived enjoyment, have a positive relationship with the intention to use visual learning. This study’s findings could provide better guidelines and be used as reference material for other education courses.